Connectivity and geopolitics: Beware the "new wine in old bottles" approach - Nadine Godehardt; Karoline Postel-Vinay (Stiftung Wissenschaft und Politik (SWP), 2020)
With the Covid-19 pandemic, the fragility and vulnerability of the liberal international order became globally visible in an instant. Aspects of everyday life and especially our taken-for-granted views of connectedness have been disrupted in Asia, Europe, and beyond. The pandemic and, more importantly, the political reactions to it, in many ways again underpin the geopolitical significance of connectivity in world politics. This link between geopolitics and connectivity becomes most obvious in a couple of successive initiatives in East Asia and the EU that illustrate the geopolitical turn of connectivity politics in the last decade. What different actors mean by connectivity matters more than ever; getting to the bottom of those meanings gives insights about what geopolitics contains today
Keywords: 320